Genital hiatus measurements predict cuff prolapse risk in prolapse surgery: Cuff prolapse risk in prolapse surgery - Şahin, Fatih; Adan, Ramazan; Bademler, Neslihan; Demirel, Elif Akkoç; Toplu, Murat İbrahim and Mihmanlı, Veli (Journal of Surgery and Medicine, 2023)
Background/Aim: Recognition and assessment of apical vaginal support defects remains a significant challenge in the evaluation and management of prolapse because there are no consensus or guidelines address the degree of apical support loss at which an apical support procedure should routinely be performed. The aim of this study was to evaluate whether preoperative genital hiatus (GH), perineal body (PB), and total vaginal length (TVL) are associated with prolapse recurrence after apical prolapse surgery. Methods: Our cohort study included 98 patients who underwent vaginal hysterectomy apical suspension due to uterovaginal prolapse of grade 2 or higher according to Pelvic Organ Prolapse Quantification (POP-Q) staging between 2020 and 2021. Patients with a history of gynecologic malignancy, those who could not tolerate surgery or anesthesia, those who had previously undergone pelvic organ prolapse surgery, those with concomitant stress urinary incontinence, and those with abnormal cervical smear results were excluded. Patients were followed for 2 years at intervals of 3 months in the first year after the surgery. The last POP-Q was performed 24 months after surgical intervention. Surgical failure or recurrence was defined as apical descent greater than one third of the total vaginal length, anterior or posterior vaginal wall past the hymen, subsequent surgery, or bothersome vaginal bulge. Patients were given the Pelvic Organ Prolapse Symptom Score (POP-SS) questionnaire before surgery and 6 months postoperatively, and the severity of symptoms was compared between the groups with and without postoperative recurrence. Logistic regression (LR) analysis was performed to determine the factors affecting recurrence. Areas under the ROC curve were calculated as a differential diagnosis for the presence of recurrence, and the predictive value (cut-off) of variables was determined using sensitivity, specificity, positive predictive value, negative predictive value, and LR (+) values. Results: While surgery was successful in 80 patients, genital relapse was seen in 18 patients. The mean preoperative perineal body was 3.05 (0.28) cm, mean preoperative GH was 3.9 (0.39) cm, and mean preoperative TVL was 8.54 (1.33) cm. The mean GH of the group with recurrence was significantly higher than the group without recurrence (P=0.004). The mean preoperative POP-SS score was 15.14 (1.86), and the postoperative POP-SS score was 4.01 (3.74). The postoperative POP-SS score mean of the recurrence (+) group was significantly higher than the group without recurrence (P<0.001). For the genital hiatus, the cut-off >4 cm had a sensitivity of 61.11%, specificity of 76.25%, positive predictive value of 36.70%, negative predictive value of 89.70%, and LR (+) value of 2.57. For POP-SS Preop-Postop Change %, the cut-off <60 had a sensitivity of 94.44%, specificity of 98.75%, positive predictive value of 94.40%, negative predictive value of 98.80%, and LR (+) value of 75.56. Conclusion: Apical vaginal support loss is highly associated with genital hiatus size. In particular, according to all study definitions, a Pelvic Organ Prolapse-Quantification measurement genital hiatus of >4 cm is a strong predictor of apical support loss. This simple measurement can be used to screen for apical support loss and further evaluate apical vaginal support before planning a hysterectomy or prolapse surgery.